PERSONALITY STRUCTURE IN THE NOVEL CLEANING CONSCIENCE BY ARIO MUHAMMAD (STUDY OF LITERATURE PSYCHOLOGY) - Afiva Rizky Pratiwi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The research of the novel Membersihkan Nurani by Ario Muhammad can be used as a reference in understanding a person’s personality and behavior. With the personality structure that occurs in the main character, it is presented in a very interesting discussion topic to study. This study aims to better understanding the personality structure experienced by the main character. The approach in this study uses the study of literary psychology. The data collection technique is done by means of semiotic analysis. This study uses analytical techniques by reading the next repeatedly by giving a sign it can be easily understood. The personality structure described in this discussion uses the psychoanalyst Sigmund Freud’s analysis. The result showed that the main character in the novel was dominated by using the super ego personality. It can be stated that my character has the strongest dominance related ti personility and emotions.